The Role of Human Resources in Library Management to Increase Student Reading Interest - Bella Adelia Ananta; Dina Risfanti; Chafidz Idris Wildan Farichi; Rusdiana Navlia (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
The importance of reading interest for students is to increase their insight. Schools provide a place for information and book collections called libraries. Libraries are managed by librarians, where librarians not only act as book lending officers. However, librarians also play a role in increasing students' interest in reading at school. The purpose of this study is to determine the role of human resources in library management to increase students' reading interest. This study uses a library research method with a descriptive qualitative approach. The results of the study show that (1) Human resources (HR) are the most important component of the library system because they determine the progress and decline of the library in carrying out its assigned functions and roles. Because HR is the main key, the quality of library HR management depends on how well they manage these human resources.; (2) Libraries play a very important role in building students' interest in reading and literacy. To achieve this, libraries provide access to books and other written resources. One of the main roles of libraries as sources of information is to encourage increased interest in reading.; (3) The role of a librarian is someone who has been appointed and given responsibility and has the ability and skills to manage a library so that they can carry out tasks related to the library. In addition, librarians play an important role in realizing an ideal library to increase students' interest in reading.